Recruitment of authoritarian individuals into clientelist networks: A comparative study of the Western Balkans - Stankov Nemanja (Anali Pravnog Fakulteta u Beogradu)
Understanding how brokers choose clients for vote-buying exchange is one of the key issues in explaining the success of these illicit practices. Norm-based theories seek an answer to this question based on individuals' values and beliefs, which would make them suitable candidates for vote-buying. A recent addition to this literature suggests that there might be a distinct authoritarian feature among the targeted voters. Building on the findings of this study, this paper examines the relationship between authoritarian tendencies and the offer of clientelist exchange in six Western Balkan countries. Overall findings vary significantly across countries: in Montenegro, Serbia, and Albania some associations were found, albeit not all in the theoretically predicted direction. In Bosnia and Hercegovina, Kosovo, and North Macedonia authoritarian tendencies were not related to an offer of clientelist exchange. The results point to a highly contextualized importance of authoritarian tendencies for the success of clientelist exchanges.